All things quilting with alex anderson ebook From first step to last stitch. - Anderson, Alex (2015)
This comprehensive guide by the host of The Quilt Show covers everything you need to know to become a master quilter. Alex Anderson has taught and inspired countless quilters around the world through her television programs, fabric lines, and numerous books. In All Things Quilting with Alex Anderson , she packs her most indispensable knowledge and advice into a single volume. Encyclopedic in its scope, it covers quilting techniques, essential tools, binding basics, piecing and appliqué, and much more. It is both a master class for novices and an essential reference for experienced quilters.